2001
DOI: 10.1007/pl00003847
|View full text |Cite
|
Sign up to set email alerts
|

On the weak Freese–Nation property of ?(ω)

Abstract: Continuing [6], [8] and [16], we study the consequences of the weak FreeseNation property of (P(ω), ⊆). Under this assumption, we prove that most of the known cardinal invariants including all of those appearing in Cichoń's diagram take the same value as in the corresponding Cohen model. Using this principle we could also strengthen two results of W. Just about cardinal sequences of superatomic Boolean algebras in a Cohen model. These results show that the weak Freese-Nation property of (P(ω), ⊆) captures many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Our formulation shows that many of the consequences of the weak Freese-Nation property of P(ω) studied in [6] already follow from SEP. We show that it is consistent that SEP holds while P(ω) fails to have the (ℵ 1 , ℵ 0 )-ideal property introduced in [2]. This answers a question addressed independently by Fuchino and by Kunen.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Our formulation shows that many of the consequences of the weak Freese-Nation property of P(ω) studied in [6] already follow from SEP. We show that it is consistent that SEP holds while P(ω) fails to have the (ℵ 1 , ℵ 0 )-ideal property introduced in [2]. This answers a question addressed independently by Fuchino and by Kunen.…”
Section: Introductionmentioning
confidence: 75%
“…A It was also proved in [6] that WFN(P(ω)) implies that a, the smallest size of a maximal almost disjoint family in P(ω), is ℵ 1 . In the proof it is sufficient to assume IDP(P(ω)).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…9 Finally, we shall mention some open problems. In [6] it is shown that a = ℵ 1 follows from WFN where a is the almost disjoint number. In [4], it is then shown that, under some additional assumptions, a = ℵ 1 already follows from SEP which is a weakening of WFN.…”
Section: A Summary Of Consistency Results and Some Open Problemsmentioning
confidence: 99%